Perbandingan Hasil Belajar Melalui Model Pembelajaran Course Review Horay, Teams Games Tournament Dan Numbered Heads Together Dengan Memperhatikan minat belajar - Ajeng Ayu Syaifa Pratiwi; Tedi Rusman; Suroto Suroto (Economic Education and Entrepreneurship Journal, 2020)
Comparative Study of Accounting Learning Outcomes Using Course Review Horay, Teams Games Tournament, and Numbered Heads Together by Seeing the Learning Interests of Class XII Students of Swadhipa Natar High School for the 2019/2020 Academic Year. This research is motivated by the low accounting learning outcomes. The purpose of this study was to determine the comparison of student learning outcomes using the Course Review Horay learning model, Teams Games Tournament, and Numbered Heads Together in accounting subjects by paying attention to the learning interests of class XII IPS at SMA Swadhipa Natar. This study uses a cooperative method with an experimental approach. The population involved in this study were all students of class XII IPS consisting of 3 classes, namely XII IPS 1, XII IPS 2, and XII IPS 3 of SMA Swadhipa Natar Academic Year 2019/2020, totaling 68 students. The sample in this study used a saturated sample, which means that the sample was taken from the entire population of 68 students. Data collection techniques through observation, documentation, questionnaires, and post-tests. Hypotheses were tested by two-way analysis of variance and two independent sample t-tests. The results of the data analysis show: (1) There are differences in the learning outcomes of students who use cooperative learning models such as Course Review Horay, Teams Games Tournament, and Numbered Heads Together. (2) The accounting learning outcomes of students whose learning uses the Course Review Horay type of cooperative learning model is higher when compared to students who use the Teams Games Tournament learning model, and Numbered Heads Together in high learning interest. (3) The accounting learning outcomes of students whose learning uses the Numbered Heads Together cooperative learning model are higher when compared to the Course Review Horay and Teams Games Tournament learning models in low learning interest. (4) There is an interaction between the learning model and students' learning interest in accounting subjects.Keywords: Course Review Horay, Numbered Heads Together, Teams Games Tournament, Accounting Learning Outcomes, and interest in learning.http://dx.doi.org/10.23960/E3J/v3i2.pp59-68